2009
DOI: 10.1021/ol901331p
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative C−C Bond Formation (Scholl Reaction) with DDQ as an Efficient and Easily Recyclable Oxidant

Abstract: DDQ in the presence of an acid is known to oxidize a variety of aromatic donors to the corresponding cation radicals. Herein, we now demonstrate that the DDQ/H(+) system can be effectively utilized for the oxidative C-C bond formations or biaryl synthesis. The efficient preparation of a variety of polyaromatic hydrocarbons including graphitic hexa-peri-hexabenzocoronenes, ease of isolation of the clean products, and ready regeneration of DDQ from easily recovered reduced DDQ-H(2) advances the use of DDQ/H(+) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
185
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(195 citation statements)
references
References 39 publications
1
185
0
5
Order By: Relevance
“…At this point we reasonedt hat an acid additive could boost the oxidative processesb yo AC in as imilar mannera ss toichiometrico xidative couplings with 2,3-dichloro-5,6-dicyano-1,4-quinone (DDQ) benefit from the addition of an acid. [22] Pleasingly,a fter adding 5equivalents of methanesulfonica cid to the reactionm ixture we were able to obtain 3,3'-bibenzofurans and 3,3'-bibenzothiophenes from good to excellenti solated yields at lower temperatures (Table 3, entries1-7). Again, without oAC, no reactionw as observed with the MsOH additive.…”
Section: Scopeoft He Reactionmentioning
confidence: 90%
“…At this point we reasonedt hat an acid additive could boost the oxidative processesb yo AC in as imilar mannera ss toichiometrico xidative couplings with 2,3-dichloro-5,6-dicyano-1,4-quinone (DDQ) benefit from the addition of an acid. [22] Pleasingly,a fter adding 5equivalents of methanesulfonica cid to the reactionm ixture we were able to obtain 3,3'-bibenzofurans and 3,3'-bibenzothiophenes from good to excellenti solated yields at lower temperatures (Table 3, entries1-7). Again, without oAC, no reactionw as observed with the MsOH additive.…”
Section: Scopeoft He Reactionmentioning
confidence: 90%
“…As a molecular model, we chose the hexa‐ peri ‐hexabenzocoronene (HBC) platform, which represents a substructure of the graphene sheet with a graphene‐like π surface (Figure 1). 22, 23, 24, 25, 26, 27, 28, 29 Prior to the reaction with alkyl iodides, HBC was activated by transformation to the dianion (HBC 2− ). We have also used hexa‐ tert ‐butylated HBC ( t Bu‐HBC) as the starting material, in which the tert ‐butyl groups provide enhanced solubility and shielding of the periphery (Figure 1 c).…”
mentioning
confidence: 99%
“…[20] As shown in Scheme 3, the [5]helicene derivatives 9 a-h could be selectively cyclodehydrogenated by DDQ to give the dehydro [5]helicenes 10 a-h in quantitative yields in both trifluoroacetic acid and trifluoromethanesulfonic acid systems. Moreover, it was found that the dehydrogenation only took 5-30 min; however, longer reaction time and more oxidant (up to 1.5 equiv DDQ) were needed for the [5]helicene derivatives with electron-withdrawing groups in the substituted aromatic subunits.…”
mentioning
confidence: 99%